Effect of Consultation and Educating in Preparation Classes for Delivery on Pregnancy Consequences: A Randomized Controlled Clinical Trial - Karimi, Simin (Electron Physician, 2016)
BACKGROUND: Care during pregnancy and performing consultation for delivery preparation play an important role in improving pregnant women’s knowledge. OBJECTIVE: The purpose of this study was to investigate the effect of consultation and instruction in the preparation classes for delivery on pregnancy consequences, including choosing the type of delivery, the performed type of delivery, and infant’s weight. METHODS: This study was conducted in 2015 on 170 pregnant women who had been referred to the prenatal clinic in Hamedan. The participants were randomly divided into intervention and control groups. Eight sessions of consultation for delivery preparation were held for the women in 20 to 36 weeks of pregnancy. The control group received only the routine care. After 37 weeks of pregnancy, the participants answered a questionnaire. The infant’s weight was measured after birth. Data were analyzed Using SPSS-21 and McNemar–Bowker Test, independent t-test, chi-square test, and Fisher exact test. RESULTS: Results showed a significant statistical difference between the two groups concerning their selective and performed delivery (p<0.001). The weight of infants in the intervention group was significantly higher than that of those in the control group (p<0.001). CONCLUSION: The findings of this study showed that the consultation for delivery preparation had a positive effect on some pregnancy consequences such as selecting the type of delivery performed and infant’s weight. TRIAL REGISTRATION: The trial was registered at the Iranian Registry of Clinical Trials (http://www.irct.ir) with the IRCTID: IRCT2015012513405N9. FUNDING: The authors received no financial support for the research, authorship, and/or publication of this article.